2010
DOI: 10.1093/intqhc/mzq004
|View full text |Cite
|
Sign up to set email alerts
|

OncoRx-IQ: a tool for quality assessment of online anticancer drug interactions

Abstract: We have created and pilot-tested OncoRx-IQ, a quality assessment tool, which helps clinicians systematically evaluate the quality and information accuracy of drug databases for anticancer drug interaction information. We hope this tool can lay the groundwork for future long-term evaluation of online drug interaction information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…This approach appears more accurate than use of electronic software to identify potential drug-drug interactions. For example, in a study by Yap and colleagues, 35 four major drug databases including Micromedex.com were able to accurately identify an interaction in only 8–56% cases. Our study also has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This approach appears more accurate than use of electronic software to identify potential drug-drug interactions. For example, in a study by Yap and colleagues, 35 four major drug databases including Micromedex.com were able to accurately identify an interaction in only 8–56% cases. Our study also has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacy software and databases, however, are reported to perform less than optimally in identifying well-known, clinically relevant DDIs. 15,16 A study undertaken by Saverno et al 15 demonstrated that only 18 of 64 pharmacies evaluated (approximately 28%) were able to correctly identify eligible interactions and noninteractions using various software programs. Of the several software systems evaluated, most were unable to detect 50% of DDIs, and one program left 77% of DDIs undetected.…”
Section: Future Directionsmentioning
confidence: 99%
“…Similar flaws have been found in more widely searched databases, such as Drugs.com and Drug Digest. In a study by Yap et al, 16 4 major drug databases were evaluated for their accuracy, and the accuracy rates were as follows: Drugs.com, 34%; Medscape, 18%; Drug Digest, 8%; and Micromedex, 56%. Despite this lack of accuracy, these databases are widely used and may be viewed as a criterion standard, as illustrated by Bowlin et al…”
Section: Future Directionsmentioning
confidence: 99%
“…En imaginant qu'une majorité des professionnels de santé concernés s'approprient ce sujet, il va donc falloir réfléchir à la définition de l'outil idéal. Cela pourrait passer par une étude de ceux qui existent et de la recherche parmi ceux-ci de celui qui est le plus avancé et le plus performant [39][40][41]. Cela passera aussi par une réflexion sur le caractère exhaustif ou non du contenu de la base qui l'alimente et les modalités de sa mise à jour [42,43].…”
Section: Matériels Et Méthodesunclassified